THER-26. PHARMACOKINETIC AND UPDATED OUTCOME DATA FROM PNOC-002: A SAFETY STUDY OF VEMURAFENIB, AN ORAL INHIBITOR OF BRAFV600E, IN CHILDREN WITH RECURRENT/REFRACTORY BRAFV600E MUTANT BRAIN TUMORS. (23rd April 2019) - Nicolaides, Theodore; Margol, Ashley; Gajjar, Amar; Goldman, Stewart; Gauvain, Karen; Kilburn, Lindsay; Nazemi, Kellie; Minturn, Jane; Leary, Sarah; Whipple, Nicholas; Gururangan, Sridharan; Crawford, John; et al.
Abstract: BACKGROUND: Vemurafenib is an orally administered inhibitor of BRAF-V600E kinase approved for the treatment of BRAF-V600E mutated melanoma. We have previously presented favorable radiographic response and safety data for vemurafenib in children with BRAF-V600E mutated brain tumors and report here an update on outcomes of this cohort, as well as pharmacokinetic (PK) data of patients taking whole (n=18) or crushed (n=6) tablets. METHODS: Vemurafenib was given orally, either as crushed or whole tablets, beginning at the adult dose equivalent of 550 mg/m2, twice daily. Toxicity, PK, and response were assessed. Doses of 420 mg/m2 and 550 mg/m2 were assessed by a 3 + 3 design in a dose de-escalation study. PK plasma samples were analyzed using HPLC at Covance Inc and modeled by standard PK methods using Phoenix v8 (Certera, Princeton, New Jersey). RESULTS: PK analyses demonstrated a significant accumulation factor (approximately six-fold) over time with each vemurafenib dose. In the "crushed" tablet cohort, bioavailability was approximately 96% of that seen in patients receiving whole tablets. The steady-state area-under-the-curve (AUCss ) median (range) was 754mg*h/L (464–920) in the whole tablet cohort and 621mg*h/L (184–1043) in the crushed tablet cohort. Updated best radiographic objective responses are: one complete response (CR), eleven partial responses (PR), and seven with stable disease (SD). Sustained responses were observed for over 50 months. Patients with SD had 30% lower AUCss compared PR+CR. However, a logistic regression model using AUCss as a predictor of PR+CR was not significant given the observed variability. CONCLUSIONS: Children with BRAF-V600E mutated brain tumors treated with vemurafenib have durable responses. PK modeling confirmed similar PK paramaters in children as compared to adults treated for melanoma. Using crushed tablets to administer a liquid suspension of drug resulted in similar drug exposure to whole tablets.